Phosphorylation of the actin-binding protein profilin2a at S137 modulates bidirectional structural plasticity at dendritic spines - Cornelius, Jonas; Haak, Stefan; Rothkegel, Martin; Korte, Martin; Michaelsen-Preusse, Kristin (Frontiers in Cell and Developmental Biology, 2023)
Background: Synaptic plasticity requires constant adaptation of functional and structural features at individual synaptic connections. Rapid re-modulation of the synaptic actin cytoskeleton provides the scaffold orchestrating both morphological and functional modifications. A major regulator of actin polymerization not only in neurons but also in various other cell types is the actin-binding protein profilin. While profilin is known to mediate the ADP to ATP exchange at actin monomers through its direct interaction with G-actin, it additionally is able to influence actin dynamics by binding to membrane-bound phospholipids as phosphatidylinositol (4,5)-bisphosphate (PIP2) as well as several other proteins containing poly-L-proline motifs including actin modulators like Ena/VASP, WAVE/WASP or formins. Notably, these interactions are proposed to be mediated by a fine-tuned regulation of post-translational phosphorylation of profilin. However, while phosphorylation sites of the ubiquitously expressed isoform profilin1 have been described and analyzed previously, there is still only little known about the phosphorylation of the profilin2a isoform predominantly expressed in neurons. Methods: Here, utilizing a knock-down/knock-in approach, we replaced endogenously expressed profilin2a by (de)phospho-mutants of S137 known to alter actin-, PIP2 and PLP-binding properties of profilin2a and analyzed their effect on general actin dynamics as well as activity-dependent structural plasticity. Results and Discussion: Our findings suggest that a precisely timed regulation of profilin2a phosphorylation at S137 is needed to mediate actin dynamics and structural plasticity bidirectionally during long-term potentiation and long-term depression, respectively.